Penguatan Kapasitas Kelompok Tani Harapan Rakyat di Wilayah KPH Laiwoi Tenggara Sulawesi Tenggara - Arniawati, Arniawati; Arafah, Nur; Ahmaliun, La De; Bana, Sahindomi; Putri, Sarwinda Intan; Zulkarnain, Zulkarnain; Sakti, Abdul; Muhsimin, Muhsimin (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Social forestry is one of the strategies for empowering communities around forests that aims to reduce deforestation and poverty by fostering community internalization in state forest management. The increasing number of permits poses a challenge for the government in assessing the institutional readiness of farmer groups after the permit. This fact serves as the background for the need to carry out community service by KTH Harapan Rakyat in Kongga Mea Village, focusing on institutional strengthening. The purpose of this service activity is to encourage greater knowledge and understanding of the roles of institutions and group governance, as well as their relation to forest conservation and economic improvement opportunities through the use of HKm areas. The service method uses a participatory approach through the delivery of materials, interactive discussions, questions and answers sessions, and reflection, involving 12 participants representing groups (administrators and members), forestry extension workers, and the village government. From the activities carried out, the participants showed an increase in the knowledge and understanding of the importance of a clear organizational structure, a transparent division of management duties, and the need to formulate a productive business development plan, both in the short and long term. Increasing participants' understanding of responsible and fair collective activities. This service activity is an important means of strengthening KTH's institutional capacity. Follow-up technical assistance is recommended to strengthen the farmer groups' capacity for sustainable forest management.